Experimental study of Single Event Effects induced by heavy ion irradiation in enhancement mode GaN power HEMT. Issue 9 (August 2015) - Abbate, C.; Busatto, G.; Iannuzzo, F.; Mattiazzo, S.; Sanseverino, A.; Silvestrin, L.; Tedesco, D.; Velardi, F.
Abstract: An experimental characterization of the behavior of GaN power HEMTs during heavy ion irradiation is presented. It is demonstrated that normally off GaN power HEMTs are affected by a significant charge amplification mechanism. These devices are subjected to damages implying relevant increases of the drain leakage current. The damages are permanent and cumulative and depend on the biasing conditions. Higher voltage devices rated at 100 V and 200 V suffer from Single Event Burnouts which take place at biasing voltages lower than the maximum rated one.